2014
DOI: 10.5897/joms2014.0110
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in seawater, sediments and marine organisms in the Gulf of Chabahar, Oman Sea

Abstract: Levels of the heavy metals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 34 publications
5
25
0
2
Order By: Relevance
“…Olusola and Festus [19], reported that the concentrations of Cd, Cu, Cr, Pb and Zn in the sediment samples of coastal waters of Ondo State Niger Delta were much below the probable effect concentration of sediment metals levels. Also, by comparing the concentrations of heavy metals analyzed in the water and sediments samples, it can be concluded that heavy metals are highly accumulated in sediments than water confirming what have earlier been reported that sediments act as reservoir for all contaminants and dead organic matter depending on the sites partitioning behaviour [19,23]. Tables 3 and 4 revealed that Onne water and sediment have greater ion contents and more salty than other sampling locations although there can be natural variability such as temperature, tidal and seasonal flushing.…”
Section: Discussionsupporting
confidence: 81%
“…Olusola and Festus [19], reported that the concentrations of Cd, Cu, Cr, Pb and Zn in the sediment samples of coastal waters of Ondo State Niger Delta were much below the probable effect concentration of sediment metals levels. Also, by comparing the concentrations of heavy metals analyzed in the water and sediments samples, it can be concluded that heavy metals are highly accumulated in sediments than water confirming what have earlier been reported that sediments act as reservoir for all contaminants and dead organic matter depending on the sites partitioning behaviour [19,23]. Tables 3 and 4 revealed that Onne water and sediment have greater ion contents and more salty than other sampling locations although there can be natural variability such as temperature, tidal and seasonal flushing.…”
Section: Discussionsupporting
confidence: 81%
“…Heavy metals in marine water such as copper (Cu), zinc (Zn), lead (Pb), cadmium (Cd), chromium(Cr), iron (Fe), nickel (Ni), manganese (Mn), sulphide (S) and many more trace elements have been reported (Ponnamperuma 1984;Bazzi 2014). Unfortunately, the mechanisms involved in heavy metal tolerance by mangrove plants are poorly understood.…”
Section: Heavy Metal Exposurementioning
confidence: 98%
“…The high level of Pb in the fishing harbor of the SC could be attributed to the spill of leaded petrol from fishing boats and dust, which holds a huge amount of lead from the combustion of petrol [71][72]. The same source of metal pollution was found in the fishing harbor of the Gulf of Chabahar [72] and along the Jeddah Red Sea Coast [71]. Indeed, Pb is used in a number of industrial applications and has been used as an anti-knocking additive in gasoline and is deposited following combustion [73].…”
Section: Origin Of Trace Element Loading In Surface Waters In Three Gmentioning
confidence: 99%